N-Terminal Extension and C-Terminal Domains Are Required for ABCB6/HMT-1 Protein Interactions, Function in Cadmium Detoxification, and Localization to the Endosomal-Recycling System in Caenorhabditis elegans - Kim, Sungjin; Sharma, Anuj K.; Vatamaniuk, Olena K. (Frontiers in Physiology, 2018)
The chronic exposure of humans to toxic metals such as cadmium from food and air causes dysfunction of vital organs, neurodegenerative conditions, and cancer. In this regard, members of the ABCB sub-family of the ATP-binding cassette (ABC) transporter superfamily, ABCB6/HMT-1, are acutely required for the detoxification of heavy metals and are present in genomes of many organisms including the nematode worm, Caenorhabditis elegans and humans. We showed previously that C. elegans ABCB6/HMT-1 detoxifies cadmium, copper, and arsenic, and is expressed in liver-like cells, the coelomocytes, head neurons and intestinal cells, which are the cell types that are affected by heavy metal poisoning in humans. The subcellular localization of ABCB6/HMT-1 proteins is unclear. ABCB6/HMT-1 proteins have a distinguishing topology: in addition to one transmembrane domain (TMD) and one nucleotide-binding domain (NBD), they possess a hydrophobic N-terminal extension (NTE) domain encompassing 5-6 transmembrane spans. The role of the NTE domain in the function of ABCB6/HMT-1 in the native organism remains to be investigated. We used a versatile, multicellular model system, C. elegans, to establish the subcellular localization of ABCB6/HMT-1 and refine its structure-function studies in the native organism. We show that ABCB6/HMT-1 localizes mainly to the apical recycling endosomes and, in part, to early and late endosomes of intestinal cells. We also show that ABCB6/HMT-1 lacking the NTE domain is mistargeted to the plasma membrane and is unable to confer cadmium resistance. Although the NTE domain is essential for ABCB6/HMT-1 interaction with itself, the absence of NTE does not fully prevent these interactions. As a result, ABCB6/HMT-1 lacking the NTE domain, expressed in wild-type worms or co-expressed with the full-length polypeptide, inactivates and mistargets the full-length ABCB6/HMT-1. We also show that the 43 amino acid residue stretch at the COOH-terminus is required for the ABCB6/HMT-1 interaction with itself and cadmium detoxification function. These results suggest that both NTE and COOH-terminus must be present to allow the protein to interact with itself and confer cadmium resistance. Considering that ABCB6/HMT-1 proteins are highly conserved, this study advances our understanding of how these proteins function in cadmium resistance in different species including humans. Furthermore, these